2011
DOI: 10.1084/jem.20110121
|View full text |Cite
|
Sign up to set email alerts
|

High-level IGF1R expression is required for leukemia-initiating cell activity in T-ALL and is supported by Notch signaling

Abstract: Notch-driven expression of IGF1R promotes the growth, viability, and transplantability of T-ALL cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
112
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 66 publications
(96 reference statements)
7
112
0
1
Order By: Relevance
“…The important contribution of IGF-IR signaling to the survival of T-LBL has been recently documented [29]. In the present study, the significance of IGF-IR, as a potential molecular target in T-LBL, was stressed once again when PPP induced negative biological effects in Jurkat and Molt-3 cells.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The important contribution of IGF-IR signaling to the survival of T-LBL has been recently documented [29]. In the present study, the significance of IGF-IR, as a potential molecular target in T-LBL, was stressed once again when PPP induced negative biological effects in Jurkat and Molt-3 cells.…”
Section: Discussionmentioning
confidence: 63%
“…Importantly, a recent study has supported major contributions of IGF-IR to the survival of leukemia-initiating cells in T-LBL. This study also concluded that IGF-IR inhibitors could have a major impact on the treatment of this aggressive type of cancer in the near future [29]. Because PPP is a potent, selective inhibitor of IGF-IR that is currently being explored in clinical trials of resistant cancer patients with notable success, we set out to examine the effects of PPP on prototype T-LBL cell lines including Jurkat and Molt-3.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the TSGs and oncogenes co-enriched with increased H3K79me2 and H3K36me3 in MA9 cells were included in the MA9-K79-K36- Setd2 -DEGs. The critical functions of these TSGs and oncogenes have been reported in leukemia patients 1824 (Figures 2c and 4b, Supplementary Tables S1–S3). Moreover, pathway analysis showed that AML-related disease terms were significantly enriched in MA9-K79-K36- Setd2 -DEGs (Figure 4c), suggesting their functions in MLLr leukemogenesis.…”
Section: Resultsmentioning
confidence: 77%
“…Co-culture with ECs induced transcripts characteristic of LICs, including CD44, IGF1R and CSF1R (Hanahan and Weinberg, 2011; Medyouf et al, 2011) (Figure 1I, Table S1). Flow cytometry analysis and quantitative PCR (qPCR) confirmed that EC coculture-mediated upregulation of corresponding proteins was due to generation of a CD44 + IGF1R + CSF1R + LC subset (Figures 1J, S1F–G).…”
Section: Resultsmentioning
confidence: 99%
“…Notch signaling is a pivotal modulator of lymphomagenesis (Aster et al, 2008; Espinosa et al, 2010; Liu et al, 2010; Lobry et al, 2013), enhancing Myc activity and upregulating receptors such as IGF1R (Medyouf et al, 2011; Weng et al, 2006). The Jagged (Jag) and Delta-like (Dll) families of Notch ligands induce Notch signaling (Gridley, 2010; Siekmann and Lawson, 2007).…”
Section: Introductionmentioning
confidence: 99%